A Plastid-Bound Ankyrin Repeat Protein Controls Gametophyte and Early Embryo Development in Arabidopsis thaliana - Kulichová, Katarína; Pieters, Janto; Kumar, Vinod; Honys, David; Hafidh, Said (Frontiers in Plant Science, 2022)
Proplastids are essential precursors for multi-fate plastid biogenesis, including chloroplast differentiation, a powerhouse for photosynthesis in plants. Arabidopsis Ankyrin-repeat protein (AT5G66055, AKRP), is a plastid-localised protein with putative function in plastid differentiation and morphogenesis. Loss of function akrp leads to embryo developmental arrest. Whether AKRP is critical pre-fertilization has remained unresolved. Using reverse genetics, here we report a new allele, akrp-3, that exhibit reduced frequency of mutant embryos (<13%) compared to previously reported alleles. Instead, akrp-3 affected both male and female gametophytes resulting in reduced viability, incompetence in pollen tube attraction, altered gametic cell fate and embryo arrest that is depleted of chlorophyll. AKRP is widely expressed and AKRP-GFP fusion localized to plastids of both gametophytes, in isolated chloroplast and co-localized with a plastid marker in pollen and pollen tubes. Cell-type specific complementation of akrp-3 hinted at the developmental timing at which AKRP might play an essential role. Our findings provide plausible insight on the crucial role of Ankyrin-repeat protein in the differentiation of both gametophytes and coupling embryo development with chlorophyll synthesis.